Heart rate variability： a new tool to predict complications in adult cardiac surgery - Nenna, Antonio; Lusini, Mario; Spadaccio, Cristiano; Nappi, Francesco; Greco, Salvatore Matteo; Barbato, Raffaele; Covino, Elvio; Chello, Massimo (Journal of geriatric cardiology : JGC, 2017)
Heart rate variability （HRV） refers to the variations between consecutive heartbeats, which depend on the continuous modulation of the sympathetic and parasympathetic branches of the autonomic nervous system. HRV has been shown to be effective as a predictor of risk after myocardial infarction and an early warning sign of diabetic neuropathy, and in the cardiology setting is now recognized to be a useful tool for risk-stratification after hospital admission and after discharge. Recent evidences suggest that HRV analysis might predict complications even in patients undergoing cardiac surgery, and the present review summarizes the importance of HRV analysis in adult cardiac surgery and the perspectives for HRV use in current clinical practice. Although future larger studies are warranted before HRV can be included into daily clinical practice in adult cardiac surgery, HRV is a novel tool which might detect autonomic instability in the early postoperative phase and during hospital stay, thus predicting or prompt-diagnosing many of the post-operative complications.